2021
DOI: 10.1016/j.injury.2021.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the Haraguchi classification in posterior malleolar fractures in A0 44-C type ankle fractures

Abstract: Better outcome for suture button compared with single syndesmotic screw for syndesmosis injury: five-year results of a randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…The analysis showed that multifragmentary trans-syndesmotic and supra-syndesmotic trimalleolar ankle fractures (AO/OTA type 44B3.3 and 44C) were more likely to receive external fixation. Interpreting this result as an expression of higher instability and therefore higher severity, this finding corresponds to the current literature, reporting a larger number of intraarticular lesions, involvement of the posterior malleolus and worse outcomes in high-grade unstable ankle fractures [ 14 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The analysis showed that multifragmentary trans-syndesmotic and supra-syndesmotic trimalleolar ankle fractures (AO/OTA type 44B3.3 and 44C) were more likely to receive external fixation. Interpreting this result as an expression of higher instability and therefore higher severity, this finding corresponds to the current literature, reporting a larger number of intraarticular lesions, involvement of the posterior malleolus and worse outcomes in high-grade unstable ankle fractures [ 14 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 88%
“…Nowadays, treatment recommendations for trimalleolar ankle fractures focus on the configuration of the posterior malleolus; therefore, the results of this study advocate the use of the Bartoníček classification as a reliable tool to guide treatment. To our knowledge, the presented study includes the largest number of patients to evaluate the reliability of classification systems in ankle fractures [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations